PENGEMBANGAN MEDIA PEMBELAJARAN BENTENGAN MATEMATIKA YANG DIPADUKAN DENGAN STRATEGI RQS - Midya Yuli Amreta (Program Studi Pendidikan Matematika, STKIP Bina Bangsa Getsempena, 2019)
This study aims to produce learning media with mathematics that are valid, practical, and effective mathematics subjects for grade IV elementary school material integer counting operations which include multiplication, division, addition, and subtraction developed and taught through the RQS strategy (Read-Question- Summary). This type of research is development research. The development model used is the 4-D (Four-D Model) model of development results tested by the One Group Pretest-Postest Design design. The results showed that: (1) the results of the validation of learning media with mathematics by the validator showed that the mathematics learning media were valid and feasible to use, (2) the application of learning media to mathematics supports learning activities, this was based on: (a) Implementation of good lesson plans (the average for grades IV-A and VI-B is 3.64 and 3.49) with a maximum score of 4; (b) barriers that occur in the learning process to overcome good by the teacher with several solutions; (c) students' response to learning is positive (the average percentage of students interested in learning is 97%; (d) all students complete their learning outcomes individually or classically, all students are in the same way as individuals with a class average of 97.33 in class IV-A and 94 , 2 in class VB, while the classical completeness is completed with a percentage of 100%. Abstrak Penelitian ini bertujuan untuk menghasilkan media pembelajaran bentengan matematika yang valid, praktis, dan efektif mata pelajaran matematika untukkelas IV Sekolah Dasar materi operasi hitung bilangan bulat yang meliputi perkalian, pembagian, penjumlahan, dan pengurangan yang dikembangkan dan dibelajarkan melalui strategi RQS(Read-Question-Summary). Jenis penelitian ini merupakan penelitian pengembangan. Model pengembangan yang digunakan adalah model 4-D (Four-D Model) hasil pengembangan diuji dengan rancangan penelitian One Group Pretest-Postest Design. Hasil penelitian menunjukkan bahwa: (1) hasil validasi media pembelajaran bentengan matematika oleh validator menunjukkan bahwa media pembelajaran bentengan matematika valid dan layak digunakan, (2) penerapan media pembelajaran bentengan matematika menunjang kegiatan pembelajaran, hal ini didasari oleh: (a) Keterlaksanaan RPP baik (rata-rata pada kelas IV-A dan VI-B adalah 3,64 dan 3,49) dengan skor maksimal adalah 4; (b) hambatan-hambatan yang terjadi dalam proses pembelajaranmampudiatasibaik oleh guru denganbeberapasolusi; (c) respon siswa terhadap pembelajaran adalah positif (persentase rata-rata siswa yang tertarik dengan pembelajaran adalah 97%; (d) semua siswa tuntas hasil belajarnya secara individual maupun klasikal,semuasiswatuntassecaraindividudengan rata-rata kelas97,33 pada kelas IV-A dan 94,2 pada kelas V-B. Sedangkanketuntasanklasikalpada tuntasdenganpersentase 100%. Kata kunci: Media Pembelajaran Bentengan Matematika, Strategi RQS (Read-Question-Summary), Hasil Belajar Kognitif